Analysis of the Drug-Resistant Tuberculosis Patients Support Program in Palembang City hy Community Community, Palembang City Based on The William Dunn Model - putri, adisty maharani (Preventif : Jurnal Kesehatan Masyarakat, 2025)
Drug-resistant tuberculosis (DR-TB) is a major challenge in TB control in Indonesia. Palembang City recorded the highest cases of DR-TB in South Sumatra in 2023 with 96 cases and a treatment success rate of only 58.97%. Based on Presidential Regulation No. 67 of 2021, the community has an important role in TB control. The purpose of this research is to evaluate the responsiveness, accuracy, equity, and adequacy of the drug-resistant tuberculosis patient accompaniment program in achieving successful treatment in the Healthy Society Community of Sriwijaya City Palembang using the policy evaluation criteria of William Dunn (2003). This research method uses a qualitative research type with a descriptive design. Data collection through interviews, observations, and literature studies. The research results show that service adequacy has reached remote areas, but geographical barriers still exist. Access has been leveled out, but there are still gaps for mono-resistant patients. Program responsiveness is quite good, but coordination with the health department needs to be improved. In terms of accuracy, the ability to implement the program has been aligned with national policies. The conclusion of this study is that the TB patient mentoring program has been quite effective, but there are still obstacles to access and cross-sector collaboration.